1997
DOI: 10.1021/om970663y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of σ-Alkynyl/P-Bonded Phosphinoalkyne Platinum Complexes toward cis-[M(C6F5)2(thf)2] (M = Pt, Pd)

Abstract: The reactivity of cis-bis(alkynyl)bis((diphenylphosphino)alkyne)platinum(II) complexes cis-[Pt(C⋮CR)2L2] (R = Ph, But; L = PPh2C⋮CPh (L1), PPh2C⋮CBut (L2); 1−4), formed by displacement of the COD ligand from [Pt(C⋮CR)2(COD)], toward cis-[M(C6F5)2(thf)2] (M = Pt, Pd, thf = tetrahydrofuran; in both a 1:1 and 1:2 molar ratio) has been investigated. Treatment of 1−4 with 1 equiv of cis-[M(C6F5)2(thf)2] affords dinuclear derivatives [{L2Pt(μ-η1:η2-C⋮CR)2}M(C6F5)2] (5−12) with exclusive formation of doubly alkynyl-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
52
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 77 publications
10
52
0
Order By: Relevance
“…DFT calculations (B3LYP/6-31G(d,p)) indicated that the P-donor ability of the simplest trialkynylphosphine P(C¸CH) 3 is comparable with that of the triphenylphosphite P(OPh) 3 . According to the 31 P NMR spectra of the hollow-shaped triethynylphosphines (L1, ¹85.2 ppm; L2, ¹83.0 ppm; L3, ¹86.5 ppm; L4, ¹81.8 ppm, in CDCl 3 ), substitution of the Si with C atom caused only marginal differences in the electronic properties (electron density and hybridization) of the central P atom.…”
Section: Ligand Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…DFT calculations (B3LYP/6-31G(d,p)) indicated that the P-donor ability of the simplest trialkynylphosphine P(C¸CH) 3 is comparable with that of the triphenylphosphite P(OPh) 3 . According to the 31 P NMR spectra of the hollow-shaped triethynylphosphines (L1, ¹85.2 ppm; L2, ¹83.0 ppm; L3, ¹86.5 ppm; L4, ¹81.8 ppm, in CDCl 3 ), substitution of the Si with C atom caused only marginal differences in the electronic properties (electron density and hybridization) of the central P atom.…”
Section: Ligand Propertiesmentioning
confidence: 99%
“…Tsuji and co-workers reported that bowl-shaped phosphine ligands, 11 which bear m-terphenyl-based P substituents, accelerated markedly the rhodium-catalyzed hydrosilylation of ketones compared to the effects of ordinary phosphine ligands such as PPh 3 and P(t-Bu) 3 , and proposed that a mono-P-ligated rhodium species was responsible for the acceleration. 12 We also reported a similar ligand-acceleration effect by bulky isocyanides 13 and silica-supported caged trialkylphosphine Silica SMAP.…”
Section: Rhodium-catalyzed Hydrosilylation Of Ketonesmentioning
confidence: 99%
See 2 more Smart Citations
“…By using the triple bond of the alkynyl ligand, a good number of di-and triplatinum complexes in which the Pt(II) centers are stabilized by double bridging alkynyl systems with different conformations have been reported [18][19][20][21][22][23][24][25][26][27][28][29]. However, the reactivity of these systems has been scarcely explored.…”
Section: Introductionmentioning
confidence: 99%